Tremor Presenting in Infants and Children Aged <2 Years. (March 2022) - Strasser, Lauren; Wilson, Mitchell; Healy, Sarah; Doja, Asif
Objectives: To examine the clinical features, course, and management of children at age <2 years with tremor.Methods: Retrospective chart review of all patients aged <2 years presenting to a tertiary care neurology clinic between 2005 and 2019. Descriptive and inferential statistics were used.Results: We identified 29 children with tremor presenting at age <2 years. The mean age at onset, diagnosis and follow-up was 3.22 months (SD 3.63), 6.97 months (SD 5.44), and 10.83 months (SD 5.29), respectively. Tremor was more noticeable surrounding eating, sleep, or extreme emotions. The tremor did not interfere with development or require pharmacologic treatment in any patient. At follow-up, 31% had complete resolution of their tremor with the rest being stable or improved. Patients with resolved tremor were statistically more likely to have a younger age of diagnosis ( F  = 3.895, P  = .033), no medical history ( P  = .029, χ 2  = 7.112), and leg tremor ( P  = .028, χ 2  = 7.143).Conclusion: Tremor with onset at age <2 years follows a benign course, with many patients requiring no treatment and outgrowing the disorder.